2021
DOI: 10.3389/fonc.2021.638802
|View full text |Cite
|
Sign up to set email alerts
|

CUL4B Promotes Temozolomide Resistance in Gliomas by Epigenetically Repressing CDNK1A Transcription

Abstract: Resistance to temozolomide (TMZ), the first-line chemotherapeutic drug for glioblastoma (GBM) and anaplastic gliomas, is one of the most significant obstacles in clinical treatment. TMZ resistance is regulated by complex genetic and epigenetic networks. Understanding the mechanisms of TMZ resistance can help to identify novel drug targets and more effective therapies. CUL4B has been shown to be upregulated and promotes progression and chemoresistance in several cancer types. However, its regulatory effect and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The U-118 MG glioma cell line is described as being resistant to TMZ up to 100 µM, or even 250 µM concentration, after 24 and 48 h incubation [ 32 , 33 , 34 ]. Our cytotoxicity studies confirmed that TMZ had no effect on the viability of these cells after 24 h incubation in the range of 25–200 µM concentration.…”
Section: Resultsmentioning
confidence: 99%
“…The U-118 MG glioma cell line is described as being resistant to TMZ up to 100 µM, or even 250 µM concentration, after 24 and 48 h incubation [ 32 , 33 , 34 ]. Our cytotoxicity studies confirmed that TMZ had no effect on the viability of these cells after 24 h incubation in the range of 25–200 µM concentration.…”
Section: Resultsmentioning
confidence: 99%
“…As SNB19 and U373 cells are resistant to TMZ action and TMZ-loaded complexes were not the ones decreasing SNB19 and U373 cellular viability the most and given that these complexes were able to promote activation of caspases, most probably, a senescence phenomenon took place in these cells due to TMZ treatment. According to published studies, TMZ drug can induce apoptosis, but it also activates survival pathways such as senescence [ 98 , 99 ]. Considering that MGMT protein may exert an important role in TMZ resistance, it would be advantageous to test MGMT expression in the investigated cell lines [ 34 , 100 ].…”
Section: Resultsmentioning
confidence: 99%
“…activation of caspases, most probably, a senescence phenomenon took place in these due to TMZ treatment. According to published studies, TMZ drug can induce apop but it also activates survival pathways such as senescence [98,99]. Considering that M protein may exert an important role in TMZ resistance, it would be advantageous t MGMT expression in the investigated cell lines [34,100].…”
Section: Tf-wrap5/pdna and Tmz/tf-wrap5/pdna Complexes Enhance Apopto...mentioning
confidence: 99%
“…4,5 Chemotherapy is an important adjuvant treatment for glioma, but the efficacy of traditional first-line chemotherapy drugs, including temozolomide, in glioma cases is less than 60%, and their toxicity and side-effect profiles bring an additional health burden to patients. 6 Because of unsatisfactory results with front-line agents, some researchers have begun to explore the inhibitory effects of traditional Chinese medicines on tumors. Some traditional Chinese medicines have been proven not only to lead to lower decreases in patient quality of life, but also to have considerable potent anticancer effects.…”
mentioning
confidence: 99%